Human trafficking, structural violence, and resilience ethnographic life narratives from the Philippines - Lennox, Amie L. (New York, NY Routledge, 2023)
"This book explores and examines human trafficking in Eastern Mindanao in the Philippines, and the social conditions which facilitate and maintain this exploitation. Through a combination of ethnographic research and life-narrative interviews, the book tells the stories of those who have experienced exploitation, and analyses the social conditions which form the context for these experiences. This book places the trafficking of migrants in context of the local social setting where migration, including human trafficking of migrants, is one of the limited options available for work. It explores how these social configurations contribute to exploitation both domestically and internationally. This book also draws on first-person accounts from those who have experienced trafficking or exploitation, offering lived experiences which reveal deep and complex cultural, social, and personal expressions of meaning, resilience, and hope within constrained, unequal, and even violent circumstances. This book will appeal to students and scholars researching and studying in the fields of social and cultural anthropology and Southeast Asian studies"--
Includes bibliographical references and index.
Keywords: Human trafficking -- Philippines; Human trafficking victims -- Philippines -- Social conditions; Philippines -- Social conditions -- 21st century